PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR MELEMPAR BOLA DALAM PERMAINAN KASTI PADA SISWA KELAS V SD NEGERI JUBELAN 02 KECAMATAN SUMOWONO KABUPATEN SEMARANG TAHUN PELAJARAN 2012/2013 - Setiaji, Endarian (Jurnal Phederal Penjas, 2012)
The purpose of this research is to improve the learning outcomes of throwing a ball in a game of rounders in class V Jubelan SD Negeri Semarang District 02 District Sumowono school year 2012/2013 by applying the model of Cooperative Learning. This research is a classroom action research (CAR). Data sources are from teachers, peers, and students. The data collection technique is to test and observation. The validity of data using triangulation techniques methods.Data analysis using descriptive techniques by using techniques percentage to see trends dlam learning process. Research procedures are interrelated spiral model. The results showed that through the application of Cooperative learning model to improve learning outcomes in the game throwing the ball rounders in class V Jubelan Elementary School District 02 District Sunowono Semarang Academic Year 2012/2013. From the analysis results obtained are improved pitching ability and mastery learning outcomes of students from prasiklus the first cycle and from cycle I to cycle II. The conclusions of this research is the application of cooperative learning model to improve learning outcomes in the game of baseball pitching in the fifth grade elementary school students JubelanSumowono Semarang District 02 District school year 2012/2013. Key words: learning models kooparatif, pitching baseball games, learning outcomes